Power, Knowledge, and Orthodoxy: The Jadal between Imam Al-Suyuti and Sultan Qaitbay and its Impact on shaping Ethical premises in Fifteenth-Century Egyptian Society - Muhammed Thameem (22257449) (2025)
This conference contribution was presented by Muhammed Thameem, Darul Huda Islamic University, India. (International Conference on Debate and Dialogue. An Initiative of QatarDebate 2025). This paper examines the dialectical engagement (jadal) between Imām Jalāl al-Dīn al-Suyūṭī and the Mamlūk Sulṭān Qāytbāy, not as a personal conflict but as a critical moment in the shaping of religious orthodoxy and moral authority in fifteenth-century Egyptian society. Moving beyond reductive readings that depict al-Suyūṭī as confrontational, this study frames their dispute—centered on issues such as the ṭaylasān and royal visitations—within the discursive tradition of Islamic thought. Drawing on Michel Foucault’s theory of knowledge-power and Talal Asad’s anthropology of Islam, the article situates this exchange within a broader framework of power dynamics, ethical deliberation, and the formation of orthodoxy. Through historical and anthropological analysis of archival texts, this research highlights how Islamic moral boundaries and social values were negotiated through scholarly and political debates. In doing so, it contributes to a deeper understanding of how discursive traditions and power structures co-constitute religious authority in Islamic societies. Other Information Conference information: The 2nd International Conference on Debate & Dialogue : An Initiative of QatarDebate (19 - 20 May 2025, Qatar National Conventions Center - QNCC, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://qatardebate.org/programs/academic-programs/2nd-icdd/